Exploring diversity: a review of animal models for investigating variations in sex characteristics - de Faria Oliveira, Gabriela; Niepsuj, Thomas; Gupta, Arushi; Auger, Anthony P. (Frontiers in Pediatrics, 2025)
This review examines mechanisms across various organisms to enhance comprehension of Variations in Sex Characteristics (VSCs) and suggests suitable models for investigation. VSCs are the result of a collection of congenital conditions characterized by atypical development of both internal and external reproductive structures. These conditions may arise from variations in genes, developmental processes, and hormonal influences. Animal models are crucial for studying VSCs due to their ability to provide valuable insights into the underlying mechanisms in which sexual differentiation exists. Comparative research across species has further emphasized the nature of certain sex-determining genes and pathways, providing a broader understanding of the evolutionary conservation of sexual differentiation mechanisms. By integrating findings from diverse animal models, encompassing the genetic, molecular, and comparative perspective, this review seeks to provide a cohesive understanding of the complex processes underlying VSCs in animals, with implications for translational research and potential treatments.